Sex differences in performance and performance-determining factors in the Olympic winter endurance sports - Strøm Solli, G.; Sandbakk, Ø.; McGawley, K. (Sports Medicine - Open, 2024)
Background Most sex comparisons in endurance sports have been derived from performance-matched groups of female and male athletes competing over similar distances within summer sports. Corresponding analyses of sex differences in winter endurance sports have not previously been conducted. In the Olympic Winter Games (OWG), the endurance sports include cross-country skiing (XCS), biathlon (BIA), Nordic combined (NC), ski mountaineering (SkiMo) and long-track speed skating (SpSk). The aim of this narrative review is to provide a comprehensive analysis of the sex differences in performance and performance-determining factors in the OWG endurance sports.